Perspective-Taking With Deictic Motion Verbs in Spanish: What We Learn About Semantics and the Lexicon From Heritage Child Speakers and Adults - Goldin, Michele; Syrett, Kristen; Sanchez, Liliana (Frontiers in Psychology, 2021)
Certain lexical expressions encode the perspective of a discourse participant. In English, deictic verbs of motion such as 'come' can encode the perspective of the speaker, or another individual, such as the addressee or a narrative protagonist, at a salient reference time and location, in the form of an indexical presupposition. Spanish, however, has stricter requirements on licensing conditions for 'venir' (‘to come’). An open question is how a dual language learner reconciles these diverging language-specific restrictions. We face this question head on by investigating narrative productions of young heritage Spanish speakers relative to English and Spanish monolingual adult and child baselines. We find that heritage speakers produce English-like patterns of 'venir' in linguistic contexts where most Spanish monolingual speakers do not—and yet, their pattern does resemble that of young Spanish speakers of a certain dialect. At the same time, however, the range of verbs in their productions, their narrative proficiency, and their word order topicalization strategies align with Spanish monolinguals, suggesting robust competence. Given this pattern, we follow up with two acceptability studies in Spanish assessing adult participants’ judgments of 'venir' in similar contexts, and find that they are willing to accept 'venir' in contexts in which they do not produce it, leading us to argue that 'venir' is not obligatorily speaker-oriented in Spanish, as claimed in the theoretical literature, and that there is dialectal variation on its usage, made clear in production and judgment data. For the heritage bilinguals, the more dominant language (English) licenses this variety of Spanish, permitting the use of a Spanish verb in a way that is dependent on the context.